THE POLITICAL CONNECTIONS AND EARNINGS QUALITY IN INDONESIA: A SURVEY LITERATURE - Yeasy Darmayanti; Aza Azlina Md Kassim; Suryadimal Suryadimal (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2020)
Providing information about quality earnings is the obligation of every company. Many factors are thought to affect the quality of earnings information issued by the company. One of these factors is political connections. Many studies see political connections from different perspectives. Some research indicates political connections will benefit individuals who carry out roles in politics and companies. Some more research has found that political connections will benefit the company. Apart from all that, of course the quality of profits disclosed by the company becomes questionable. This research contributes to providing a detailed review of different studies on the relationship of political connections and earnings quality, and tries to describe in more detail the matters relating to both. In the future, this new diagnostic system may be investigated in different contexts.